EM-Act: A Modular Series Elastic Actuator for Dynamic Robots - Ramesh krishnan Muttathil Gopanunni; Lorenzo Martignetti; Francesco Iotti; Alok Ranjan; Franco Angelini; Manolo Garabini (IEEE Open Journal of the Industrial Electronics Society)
The trend of current robotic research is to develop mobile robots that can perform highly dynamic tasks, which include jumping and running. To be employed profitably, this research necessitates a significant amount of work in the development of innovative planning and control algorithms that need experimental validation on actual robots. However, the majority of robots with highly dynamic performance capabilities are currently restricted to a few expensive platforms. This is a major obstacle that ultimately restricts the amount of contributors and the advancement of the research. Thus, a cost-effective actuator solution is needed that is also able to execute very dynamic movements. With this goal in mind, we present EM-Act, a modular series elastic actuator (SEA) for legged and multimodal dynamic robots. This work focuses on the development of the actuator solution by defining jump height as the prerequisite, identifying actuator parameters through simulations, and selecting and testing mechatronic elements of the design. The work also discusses a compact integration of desired compliance to address the impact forces. Furthermore, the work also details the implementation of the actuator solution on a 2-degree-of-freedom (DOF) robotic leg and experimentally validates its jumping performance.